How To Achieve Good Financial Governance by Reconstruction of Management Accounting Information System and Asset Management for Better Village - Narastri, Maulidah; Ratnawati, Tri; ., Hwihanus (Journal of Ecohumanism, 2025)
The purpose of this study is to reconstruct the organizational structure along with the main tasks and functions of village officials in terms of management accounting information systems for village asset management in order to create good village governance. The method used in this study is inductive. The type of research used is qualitative with a phenomenological approach. The researcher conducted field observations with a focus on digging up information on how village assets have been managed so far. The results of the study stated that there must be an additional special official who has the field of village asset management so that village assets and potential can be managed properly. To improve asset management, the village should introduce a Technical Implementer position, specifically a Head of Asset Management, with the following responsibilitie likes Administration of village assets, Inventory management, Cash flow management for asset operations, and Maintenance and preservation of village assets. Researcher hopes that there will be writing that focuses on researching villages all over the world but with different or the same topics so that there is additional insight for readers.